Keberagaman Kesadaran Belajar Sebagai Tolak Ukur Tingkat Motivasi Siswa PAUD dan SD di Kelurahan Setu - Az-Zukhruf, Amaliyah; Naziha, Berliana Maulani; Hanun, Firyal; Vironi, Via; Fajriyah, Jihanatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Education in Setu has been considered to have developed well, especially for Pendidikan Anak Usia Dini (PAUD) to Elementary School. However, the observation results showed that PAUD to Elementary School children still lacked awareness in learning. This article aimed to investigate and analyze the diversity of learning awareness as a measure of students’ motivation levels in Pendidikan Anak Usia Dini (PAUD) and Elementary School in Setu Subdistrict, South Tangerang City, Banten Province. Learning awareness is an affective, cognitive, and behavioral dimension that affects individual well-being in learning. This research was conducted on PAUD to Elementary School children with a total of 32 students, using a survey method with a questionnaire consisting of 18 written questions as a data collection technique. The collected data will be analyzed using descriptive analysis, which involves basic statistical calculations such as frequency, percentage, and average to summarize and explain the data obtained from the questionnaire. The results of this research are expected to provide a deep understanding of learning awareness among PAUD and Elementary School students in Setu Subdistrict, thus providing a foundation for improving student learning and well-being.